2005
DOI: 10.1016/j.econedurev.2004.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Schooling quality in Eastern Europe: Educational production during transition

Abstract: This paper uses student-level Third International Mathematics and Science Study (TIMSS) data to analyze the determinants of schooling quality for seven Eastern European transition countries by estimating educational production functions. The results show substantial effects of student background on educational performance and a much lower impact of resources and the institutional setting. Two different groups of countries emerge. For the first group that features high mean test scores and has progressed far in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…Similarly, in Central and Eastern Europe, bologna initiated a widespread educational paradigm which has (1) marked a move towards standardization and a concurrent upgrading of university standards to Western levels (Field 2003), and (2) initiated changes from teacher-centred instruction towards a student-centred orientation (Ash 2006). In post-socialist countries with teacher-centred education and centralized curricula, these changes might have posed greater challenges than in other parts of Europe (Silova et al 2006), which is not surprising as the new market economies demand skills and competencies that were not fostered during socialism (Ammermuller et al 2005). A case in point is our particular context (cf.…”
Section: Educational Reform and The Broader Socio-political Changesmentioning
confidence: 94%
“…Similarly, in Central and Eastern Europe, bologna initiated a widespread educational paradigm which has (1) marked a move towards standardization and a concurrent upgrading of university standards to Western levels (Field 2003), and (2) initiated changes from teacher-centred instruction towards a student-centred orientation (Ash 2006). In post-socialist countries with teacher-centred education and centralized curricula, these changes might have posed greater challenges than in other parts of Europe (Silova et al 2006), which is not surprising as the new market economies demand skills and competencies that were not fostered during socialism (Ammermuller et al 2005). A case in point is our particular context (cf.…”
Section: Educational Reform and The Broader Socio-political Changesmentioning
confidence: 94%
“…While some researchers have used composite measure of SES to conduct their analysis (Baker et al, 2002;Nonoyama-Tarumi, 2008, Nonoyama-Tarumi andWillms, 2010;Yang and Gustafsson, 2004;Chudgar and Luschei, 2009) and recommend the use of composite indices of SES (Mueller and Parcel, 1981), others assessed the SES by using a variety of items (Duncan et al, 1972;Alexander and Simmons, 1975;Heyneman, 1976a;Entwisle and Astone, 1994;Hanushek and Luque, 2003;Wö ßmann, 2003Wö ßmann, , 2004Ammermü ller et al 2005;Chiu and Khoo, 2005;Martins and Veiga, 2010) because each item of SES is supposed to be unique and supposed to capture a different aspect of SES (Sirin, 2005). Table 4 displays the different variables used to assess SES.…”
Section: Description Of Variables Usedmentioning
confidence: 98%
“…Regarding the school resources, the literature has shown that the link between students' performance and school resources is ambiguous. Furthermore, no conclusive results about which specific school resources matter and to what extent they matter were provided (Fuller, 1987;Hanushek, 1995Hanushek, , 2003Kremer, 1995;Ammermü ller et al, 2005). Two indices were provided by TIMSS 2007 The Index of availability of school resources for mathematics instruction and the index of availability of school resources for science Instruction.…”
Section: Description Of Variables Usedmentioning
confidence: 99%
“…The studies that deal with family factors include Baker et al (2002), Wößmann (2010), and Ammermüller et al (2005). In their study for Trends in International Mathematics and Science, Baker et al (2002) analyzed the learning achievement data of 36 countries and areas in arithmetic and science.…”
Section: Introductionmentioning
confidence: 99%